GE_GERICHTE C/4272/2015 vom 10. Juni 2016 - GE Cour de justice (2016)
PROTECTION DE L'UNION CONJUGALE ; OBLIGATION D'ENTRETIEN ; CONJOINT ; ENFANT ; REVENU HYPOTHÉTIQUE ; DÉBUT | CC.176.1.1; CC.176.3;